Childhood maltreatment and problematic social media use: The role of attachment and depression. (September 2018) - Worsley, Joanne D.; McIntyre, Jason C.; Bentall, Richard P.; Corcoran, Rhiannon
Highlights: Childhood maltreatment is associated with problematic social media use. Avoidant attachment was associated with less problematic use. Anxious attachment was associated with more problematic use. Avoidant attachment and depression in series accounted for part of the relationship. Anxious attachment and depressive symptoms in series fully mediated the relationship. Abstract: Childhood maltreatment is associated with many maladaptive outcomes. This study sought to examine the association between childhood maltreatment and problematic social media use using a cross-sectional sample of young adults aged 17–25 years ( n = 1029). Specifically, we studied whether the relationship is mediated through (i) attachment anxiety, (ii) attachment avoidance, or (iii) both attachment dimensions operating in series with depressive symptoms. Results revealed that a history of childhood maltreatment was significantly associated with more problematic social media use. Both anxious and avoidant attachment dimensions independently mediated the relationship between childhood maltreatment and problematic use of social media, but in opposing directions. Avoidant attachment was associated with less problematic social media use, whilst anxious attachment was associated with more problematic social media use. Avoidant attachment and depressive symptoms in series accounted for part of the relationship between childhood maltreatment and problematic social media use. Anxious attachment and depressive symptoms in series fully mediated the relationship between childhood maltreatment and problematic social media use. The results suggest that childhood maltreatment may influence social media use directly, but also indirectly. People experiencing depressive symptoms may overuse social media in an attempt to alleviate their distress. However, causality cannot be established with the current design.